The Role of Iron (Fe) in Health and Medicine: Scientific Interpretation of Surah Al-Hadid Verse 25 - Fawwaz, Muammar; Sampurno, Bambang (Pharmaceutical Reports, 2025)
Iron is a vital element for life, playing essential roles in oxygen transport, metabolism, enzymatic activity, and cognitive development. Surah Al-Hadid [57]:25 of the Qur’an references iron, which aligns with its biological, medical, and cosmic significance. This review examines the intersection of Qur’anic references, astrophysical evidence, and biomedical research related to iron, highlighting the numerical correlations between the surah number (57) and Fe-57, and verse 25 with iron’s atomic number (26). Modern astrophysics confirms that iron is synthesized in stars and delivered to Earth via supernovae, echoing the Qur’anic expression “We sent down iron”. Biologically, iron deficiency causes anemia, impaired immunity, and cognitive deficits, while iron-based therapeutics—including oral supplements, parenteral formulations, and nanoparticle-based drug delivery systems—demonstrate its crucial role in human health. Surah Al-Hadid [57]:25 exemplifies the convergence of divine revelation and scientific knowledge, encouraging ethical and informed utilization of natural elements in medicine and technology, reflecting harmony between spiritual guidance and scientific inquiry.